A planar UWB semicircular-shaped monopole antenna with quadruple band notch for WiMAX, ARN, WLAN, and X-Band - Majed O. Al-Dwairi (Institute of Advanced Engineering and Science, 2020)
This paper proposed quadruple notched frequency bands ultra-wideband (UWB) antenna. The antenna is a semicircular-shaped monopole type of a compact size 36x24 mm, covering frequency range of 3.02-14 GHz. Four rejected narrow bands including WiMAX (3.3-3.7GHz), ARN (4.2-4.5 GHz), WLAN (5.15-5.825GHz), X-Band (7.25-7.75) have been achieved using inserting slots techniques in the patch, feed line, and ground plane. The slots dimensions have been optimized for the required reject bands. The antenna design and analysis have been investigated by simulation study using CST-EM software package. The antenna characteristics including impedance bandwidth, surface current, gain, radiation efficiency, radiation pattern have been discussed.